Inhibition of bacterial virulence factors as a method of treating bacterial pneumonia - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2018)
Incremental increase in the number of antibiotic-resistant bacterial strains in the etiologic structure of pneumonia and reduced potential of antibiotic therapy increase the importance of drugs in the treatment of pneumonia, which are aimed at neutralizing virulence factors of etiologically significant bacterial agents. There are the following drug methods for monitoring the infectious process by suppressing bacterial virulence factors: inhibition of production of bacterial virulence factors, neutralizing virulence factors, blocking of receptors, blocking of receptors recognizing virulence factors. One possible method for the treatment of low-curable forms of pneumonia caused by antibiotic-resistant strains is the use of monoclonal antibodies (mAb) specific for certain antigens of respiratory-tropic pathogens. At present, technologies have been developed that make it possible to obtain fully humanized mAbs, which have a minimal level of immunogenicity and toxicity. In view of the high affinity of bacterial pore-forming toxins to the lipid bilayer of the cell membranes of the macroorganism, an alternative to specific mAbs as neutralizers of bacterial virulence factors are non-specific lipid sequestrants, wherein the experimental use of these sequestrants prevents the development of fatal septicemia.